2008
DOI: 10.1002/hep.22739
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hepatocyte engraftment and long-term transgene expression after reversible portal embolization in nonhuman primates

Abstract: The feasibility of ex vivo gene therapy as an alternative to liver transplantation for the treatment of liver metabolic diseases needs to be analyzed in large animal models. This approach requires appropriate gene transfer vectors and effective hepatocyte engraftment. Lentiviral vectors have the ability to transduce nondividing differentiated cells, such as hepatocytes, and portal vein occlusion increases hepatocyte engraftment. We investigated whether reversible portal vein embolization combined with ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 38 publications
0
43
1
Order By: Relevance
“…Usually major loss of transplanted cells is thought to be due to failure in entering sinusoids and crossing the sinusoidal-endothelial barrier [40]. In a nonhuman primate model, liver repopulation with transplanted hepatocytes was approximately 2%-7% [40], whereas in our study, robust engraftment was recorded (34.14%, 37.34%, 45.25%, and 26.16% engraftment in groups 4, 5, 6, and 7, respectively). Transplantation of stem and progenitor cell populations, rather than mature hepatocytes, has been investigated recently, exploiting their known proliferative potential.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Usually major loss of transplanted cells is thought to be due to failure in entering sinusoids and crossing the sinusoidal-endothelial barrier [40]. In a nonhuman primate model, liver repopulation with transplanted hepatocytes was approximately 2%-7% [40], whereas in our study, robust engraftment was recorded (34.14%, 37.34%, 45.25%, and 26.16% engraftment in groups 4, 5, 6, and 7, respectively). Transplantation of stem and progenitor cell populations, rather than mature hepatocytes, has been investigated recently, exploiting their known proliferative potential.…”
Section: Discussioncontrasting
confidence: 43%
“…In rats, transplantation of 2 3 10 7 hepatocytes results in engraftment of approximately 0.5% of the total recipient liver cells [39], and this hepatocyte loss occurs during the early stages of transplantation [40,41]. Usually major loss of transplanted cells is thought to be due to failure in entering sinusoids and crossing the sinusoidal-endothelial barrier [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Although we did not confirm the feasibility of the small intestine as an effective PCS component, as well as a scaffold for liver regeneration, in this study, we showed that the transplanted graft met the requirement to maintain the blood circulation and its structure for 1 month, which is needed for our strategy.…”
Section: Discussionmentioning
confidence: 65%
“…The aim of this technique is to induce the atrophy of the ipsilateral liver and thus the hypertrophy of the future remnant liver before hepatectomy. Based on these results, some teams have developed reversible portal vein embolization to avoid liver atrophy [51][52][53].…”
Section: Portal Flow Modulation In Donorsmentioning
confidence: 99%